Aldehyde dehydrogenase 1 expression is correlated with poor prognosis in breast cancer. Issue 25 (June 2017) - Yao, Juan; Jin, Qin; Wang, Xu-dong; Zhu, Hui-jun; Ni, Qi-chao
Abstract : Abstract: Breast cancer (BC) is one of the most common cancers worldwide, and is a major cause of death in women. Aldehyde dehydrogenase 1 (ALDH1) is a marker of stem cells and cancer stem cells, and its activity correlates with the outcome of various tumors, including BC. This study aimed to analyze the relationship between ALDH1 expression and clinicopathological characters in BC and the prognostic significance of ALDH1. We used quantitative reverse-transcription PCR (qRT-PCR) to detect ALDHA1 mRNA levels in 25 fresh frozen BC samples and matched noncancerous samples. Immunohistochemistry on tissue microarrays was used to analyze protein expression in 137 paraffin-embedded BC tissues and corresponding noncancerous tissues. STATA 16.0 software was used for statistical analysis. The results suggested that levels of both ALDH1 mRNA and protein in BC were significantly higher than in corresponding adjacent breast samples (3.856 ± 0.3442 vs 1.385 ± 0.1534, P < .001; 52.6% vs 25.5%, P < .001, respectively). ALDH1 protein expression was also significantly associated with histological grade ( P = .017), tumor size ( P = .017), and tumor–node–metastasis (TNM) stage ( P = .038). Multivariate analysis using the Cox regression model demonstrated that ALDH1 expression ( P = .024), molecular typing ( P = .046), and TNM classification ( P = .034) were independent predictive factors for the outcome of BC. Kaplan–Meier analysis and the log-rank test indicated that patients with high ALDH1 expression, triple-negative BC, and advanced TNM stage had a reduced overall survival time. These data suggest that ALDH1 could be used as a prognostic factor for BC and may provide a useful therapeutic target in the treatment of BC.